National-level planning in democratic countries : an international comparison of city and regional policy-making - Alterman, Rachelle (Town planning review special studies, 2001)
Based on a need for knowledge about how different countries handle spatial planning issues, this study looks at national-level planning in ten developed countries. It also identifies the degrees of co-ordination between the different sectors, and evaluates the implementation processes.